Tradition, Political and Legal Systems of Nepal - Ghimire, Tara Nath; Phuyel, Shyam Prasad (HISAN: Journal of History Association of Nepal, 2022)
This study concerns the political system, and traditional rituals practiced in Nepal. It focuses on the analysis of the unique relationship between the political system and tradition in Nepal. The Nepali legal system is based on customary law. Nepali society is largely based on the traditional framework. Perhaps all societies have been developing their social norms. Britain, which is considered the mother of democracy, has been operating its governing system according to tradition. In this way, no one would deny that the state or society is progressing in its way or pattern. In that way, I have conceptualized tradition as trends that have been practiced for a long time or accepted by people. Ancient civilizations, be those Atheinns or India, have been bound in some tradition. This study is focused on what traditions are maintained in the political and legal systems in Nepal, and how those traditional rituals have influenced today’s political system of Nepal. As a library study, it is purely qualitative in nature, and it has descriptively analyzed the secondary materials from the Middle Age to the present day.